MAQOSHID AL SYARI’AH DALAM HUKUM MAHAR PERKAWINAN - AKHMAD MAIMUN (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2023)
Abstrak: Mahar in the Koran is referred to by various terms. This varied term of dowry contains specific aims and objectives (maqashid syari'ah). To find out the maqasid syari'ah dowry, it is necessary to carry out a comprehensive study of the verses of the Koran that explain dowry. Among the verses of the Koran that explain dowries include QS. Annisa 4 and 20 and QS. Al Baqarah 237. Maqasid al Sharia as a conception in understanding the aims and objectives of Islamic shari'ah needs to be used as a basis for analysis in conducting a comprehensive study. In Ibn Asyur's maqashid al syari'ah, there are three steps that can be taken in conducting maqashid analysis, first, istiqra' (observation) of the syar'I arguments. Second, a comprehensive assessment of the arguments that have the same topic. Third, the use of mutawatir hadiths as support in conducting analysis. The results of applying Ibn Asyur's maqashid al syari'ah to the arguments regarding dowry show that the law on giving dowry aims to provide protection so that a marriage can be carried out and to provide protection for the life of a wife in the household. In addition, giving dowry needs to pay attention to the position of women in social construction.